Assessing the Economic Viability of Small-Scale Sonali Chicken (Egyptian Fahmi chicken, ♂ x Rhode Island Red, USA. ♀) Farming in Rural Bangladesh: Insights from Jamalpur District (Annals of Bangladesh Agriculture, 2025)
Poultry farming, with a focus on Sonali chicken (a cross breed of Rhode Island Red, USA ♂ and Egyptian Fayoumi ♀) production, stands as a cornerstone for poverty alleviation, employment generation, and the agrarian economy of Bangladesh. Mindful of the nation's dense population, our study meticulously examines the profitability of Sonali chicken enterprises, drawing data from 100 farmers and 100 traders operating across diverse marketing channels within the Jamalpur district. Employing a robust methodology involving semi-structured interviews and cost-return analysis, we scrutinize production costs, gross returns, and net gains. Our findings underscore the significance of variable costs, particularly attributed to feed and day-old chicks, which constitute a substantial portion of the overall production expenses, while fixed costs remain comparatively modest. Notably, the gross returns derived from live chicken sales and the utilization of by-products such as litter and excreta exhibit noteworthy profitability within Sonali chicken farming. Furthermore, through meticulous benefit-cost ratio (BCR) analysis, we corroborate the financial viability of this sector, accentuating its capacity to uplift rural livelihoods and fortify Bangladesh's poultry industry. By furnishing indispensable insights, our study serves as a compass for stakeholders and policymakers, facilitating informed decisions to support and expand the poultry domain, thereby ensuring both food security and sustainable economic development in rural spheres.